Hoe om die Bybel beter te verstaan: Verklarings van die Bybel in Afrikaans - Vosloo, W. (Verbum et ecclesia, 2001)
During the early 1920's some sporadic (and experimental) commentaries on the Bible in Afrikaans were published. However, after the Bible was translated into Afrikaans in 1933 these drops turned into a stream and soon swelled into a torrent of publications. These publications display a steady growth in Biblical understanding from a literal and even fundamentalistic interpretation to a critical exegesis of Scripture. At least three distinct phases can be demonstrated, namely a focus on the author, then on the text, and finally on the reader. Given the limited number of readers, the publication of Afrikaans commentaries in the future is faced with unique problems and decisions.